Abatement of environmental pollutants : trends and strategies - Singh, Pardeep; Kumar, Ajay, PhD; Borthakur, Anwesha (Elsevier, 2020)
Abatement of Environmental Pollutants: Trends and Strategies addresses new technologies and provides strategies for environmental scientists, microbiologists and biotechnologists to help solve problems associated with the treatment of industrial wastewater. The book helps readers solve pollution challenges using microorganisms in bioremediation technologies, including discussions on global technologies that have been adopted for the treatment of industrial wastewater and sections on the lack of proper management. Moreover, limited space, more stringent waste disposal regulations and public consciousness have made the present techniques expensive and impractical. Therefore, there is an urgent need to develop sustainable management technologies for industries and municipalities. To remove the damaging effect of organic pollutants on the environment, various new technologies for their degradation have been recently discovered. --